Chapaev and His Comrades War and the Russian Literary Hero across the Twentieth Century - Brintlinger, Angela (Cultural Revolutions: Russia in the Twentieth Century, 2012)
"Across the twentieth century war was the central experience of the Russian people, spurring tales of the struggles and advances of the combat hero to become a prevailing Russian literary trope. In this wide spanning text Brintlinger traces the war experiences, memories, tropes, and metaphors in literature of the Soviet and post-Soviet period, examining the work of Dmitry Furmanov, Fyodor Gladkov, Alexander Tvardovsky, Emmanuil Kazakevich, Vera Panova, Viktor Nekrasov, Alexander Solzhenitsyn, Vladimir Voinovich, Sergei Dovlatov, Vladimir Makanin, Viktor Astafiev, Viktor Pelevin, and Vasily Aksyonov. These authors represented official Soviet literature and underground or dissident literature. They fell into and out of favor, were exiled and returned to Russia, and died at home and abroad. Most importantly, each of these writers was touched by war and reacted to the state of war in their literary works."